(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to discover the manifestations of the phenomenon of bullying in schools and to investigate its causes. For this purpose, a tool for the manifestations and causes of bullying in schools was constructed, and its validity and reliability were examined. The study tool was applied to a sample of (340) male and female students from the seventh, eighth, ninth, and tenth grades of Marka District students for the academic year 2023/2024. They were selected using the purposeful random sampling method. Data were collected, and the Statistical Package for the Social Sciences (SPSS) was used for data processing, with percentages and frequencies extracted. The results of the study showed the following: 1. The verbal manifestation is the most common and practiced manifestation in schools, followed by the physical manifestation, then the non-verbal social manifestation, and finally the sexual manifestation. 2. The causes attributed to the victim are the highest percentage among the causes in schools, followed by the causes attributed to society, then the causes attributed to the bully.